Auxiliary functions in photosynthesis: the role of the FtsH protease. (August 2001) - Bailey, S.; Silva, P.; Nixon, P.; Mullineaux, C.; Robinson, C.; Mann, N.
Abstract : Oxygenic photosynthesis can be described effectively by using two long-standing models: the Z-scheme and the chemiosmotic hypothesis. However, these models do not reveal the dynamic nature of the thylakoid membrane and the four major complexes that it binds. The composition of the photosynthetic apparatus is continually changing in response to a range of environmental stimuli. In addition, many photosynthetic components have some of the highest turnover rates in Nature. Changes in composition and turnover of photosynthetic components require the degradation of existing and damaged polypeptides and the resynthesis and co-ordinated assembly of new polypeptides and their associated cofactors. This is achieved by several auxiliary functions, including proteolysis, protein targeting and the action of molecular chaperones. Some of the components involved in these functions, such as translocons, chaperones and proteases, have been identified but many of the auxiliary functions of photosynthesis remain uncharacterized. Among the proteases known to be associated with the thylakoids is the zinc metalloprotease FtsH, which might also act as a chaperone. Here we provide an overview of the thylakoid FtsH protease and discuss its role in the maintenance and assembly of the photosynthetic apparatus.